The earthquake effect of double storey RC building due to surrounding earthquake in Malaysia - Ainaa Nabila, Md Abd Aziz (2016)
Most structures in Malaysia do not consider for seismic design during its service lifetime. However, recently, Malaysia experienced a tremor events in Ranau, Sabah and it might be effected the structures in Malaysia by the tremors of earthquake in Malaysia and also from neighbouring countries such as Philippines, Indonesia etc. The aim of this study is to identify the behaviour of double storey reinforced concrete building that subjected to earthquake excitation. This research presents the comparative analysis between using Esteem Structural and SAP2000 software. The structure is in three-dimensional form and it is tested with dead load, live load and environmental load such as wind and current load with addition of earthquake ground accelerations from Aceh earthquake. The response of the structure due to the above loadings are illustrated and discussed. Results such as the natural frequencies, vibration modes of the structure, displacement, bending moment and shear stress, etc. are collected and analyzed for both software and be compared. From the analysis result, SAP2000 is more detailed and accurate compared to Esteem. Generally, the building structure with consideration of seismic ground motion is still within the member capacity desirable range. In summary, the double storey reinforced concrete building is yet consider safe and does not require seismic design for this moment of time.